(untitled) (Web of Teachers: Inderscience Research, 2024)
This research article investigates how Inquiry-Based Learning (IBL) is effective to teach vocabulary to intermediate level students. This article provides with information about what Inquiry-Based Learning is and whether there is a significant difference between the learning results before and after the teaching period using this method. Novelty of this research article is that an essential aspect of using the IBL approach in vocabulary learning is something new that sheds light on the group collaboration process, creativity, and engagement. In order to conduct the research two groups are chosen as an experimental group with the same level (intermediate) and taught Vocabulary using IBL method during 40 days. Pre-test and post-tests are conducted in order to measure student’s results